Estimation of Radioactivity Caused by Chemical Fertilizers on Trakya Sub-Region Soils and Its Potential Risk on Ecosystem - Bayrak, Gökçen; Keleş, Emine; Atik, Damla (European Journal of Sustainable Development, 2018)
Exposure to terrestrial radioactivity depends primarily on geological conditions and soil types. Phosphate, nitrogen and potassium fertilizers, which are used predominantly in order to increase crops in agriculture, provide basic nutrients to plants. Radionuclides in phosphate fertilizer belonging to 232Th and 238U from phosphate rocks series as well as radioisotope of potassium (40K) are the major contributors of outdoor terrestrial natural radiation. The plants take some fractions of radioactivity and radionuclides enter the food chain in this way. Trakya sub-region, located in northwestern Turkey, constitutes one of the significant agricultural centers, 65% of this area is used for agricultural purposes. This is the region which uses the most fertilizer per unit area, with an average of 145 kg per hectare and approximately 20% of the fertilizer consumed in Turkey is used in the region. The main objective of this study is to evaluate Trakya Sub-region from the point of potential environmental effects of radionuclides which may be caused by phosphate fertilizers used in agricultural areas. For this purpose, it is aimed to determine the priority areas for the monitoring studies by analyzing the results of the use of temporal and spatial fertilizers and the studies performed in the region. Keywords: Radioactivity, chemical fertilizers, Trakya Sub-region, soil